KORELASI KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR MATEMATIKA SISWA - Ahmad, Ahmad; Perwira Negara, Habib Ratu; Ayu Kurniawati, Kiki Riska (LP2M Institut Agama Islam Nurul Hakim, 2021)
The purpose of this study is to find out the correlation between emotional intelligence and student learning achievement at MTs Nurul Yaqin Kelanjur. This type of research is expos Fakto where the data analyzed comes from existing data. This research was conducted at MTs Nurul Yaqin Kelanjur Montong Sapah Village, Praya District southwest of Central Lombok Regency. The result of this study was, the highest score of emotional intelligence equaled 95, and the lowest score was 60. As for the student's learning achievement score on math subjects obtained the highest score of 92 and the lowest score of 55. From the pre-analysis tests conducted it is known that the data obtained is normal and homogeneous. The results of hypothesis tests conducted showed that emotional intelligence has a positive and significant correlation with students' math learning achievement.